Menelaah Kebijakan Publik dalam Upaya Mewujudkan Kesejahteraan Masyarakat di Indonesia (Studi Literatur) - Dinda Aprilia Putri; Hasbullah Malau (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
Public policy is the government's responsibility in carrying out its duties. Public policy is closely related to the welfare and survival of the people. Public policy implemented properly and correctly by the government will impact society and the progress of the nation.The method used in writing this article is a literature review, which involves collecting and analyzing various scientific articles, journals, and other sources discussing public policyIndonesia implements public policy models that take into account the context of decentralization, social diversity, and political dynamics in Indonesia. This implementation often faces challenges related to data, resources, and diverse interests. Public policies in Indonesia are very diverse, covering the health sector (JKN), education (APBN fund allocation), transportation (Traffic Law), the environment (paid plastic bags), the economy (tax incentives, product protection), and public services (taxes, administration) to regulate national life, improve welfare, and create social order in accordance with the mandate of the law and the needs of the times. Furthermore, supporting factors for public policy implementation include aspects of communication, authority/bureaucratic structure, resources, and the disposition or attitude of the implementer. Meanwhile, inhibiting factors consist of internal factors such as corruption, external factors such as lack of public participation, and policy factors such as policy ambiguity.